2016
DOI: 10.1093/ndt/gfw076
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase 9 is associated with peritoneal membrane solute transport and induces angiogenesis through β-catenin signaling

Abstract: Our data suggest that MMP9 is involved in peritoneal membrane injury possibly through cleavage of E-cadherin and induction of β-catenin signaling. MMP9 is a potential biomarker for peritoneal membrane injury and is a therapeutic target to protect the peritoneal membrane in PD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 53 publications
3
23
0
Order By: Relevance
“…It is well known that the disruption of adherent junctions is an early step and one of the key events in MMT23. In this context, it has been reported that MMT and peritoneal membrane injury are mediated through cleavage of E-cadherin by MMP-9 and induction of β-catenin signaling32. Interestingly, we observed that the Wnt/β-catenin pathway was deregulated in both E and NE cells (Fig.…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…It is well known that the disruption of adherent junctions is an early step and one of the key events in MMT23. In this context, it has been reported that MMT and peritoneal membrane injury are mediated through cleavage of E-cadherin by MMP-9 and induction of β-catenin signaling32. Interestingly, we observed that the Wnt/β-catenin pathway was deregulated in both E and NE cells (Fig.…”
Section: Resultssupporting
confidence: 52%
“…Interestingly, peritoneal transport of the PD patients from whom the cells were harvested was associated with the ex vivo expression levels of molecules that were over-expressed during MMT in cultured effluent MC2427. As a proof of concept, levels of MMT-associated molecules in the PD effluent, including VEGF, CTGF/CCN2, Gremlin-1 (GREM1), and MMP9 were found to correlate with the peritoneal transport status2829303132. Herein, by using whole genome microarray analysis of MCs undergoing MMT in vitro and ex vivo , we aimed to identify novel molecular biomarkers that may facilitate diagnosis of the integrity and functionality of the patient’s peritoneum and hence allow early adaption of treatment to the patient’s needs.…”
mentioning
confidence: 98%
“…Angiogenesis is one of the pathologic consequences following long-term PD [ 4 ]. Previous studies suggested that VEGF expression is also implicated in peritoneal fibrosis [ 4 , 41 ]. To investigate whether HDAC6 inhibition is involved in angiogenesis, we examined the expression level of CD31 (a marker of endothelial cells) and VEGF by immunohistochemistry.…”
Section: Resultsmentioning
confidence: 99%
“…Degradation of the vascular basement membrane is an indispensable step for the invasion of endothelial cells. An increase in MMPs is associated with tumour invasion, metastasis and angiogenesis (38). Among the proteolytic enzymes, MMP9 has been reported both in vivo and in vitro, to have an important role in angiogenesis.…”
Section: Discussionmentioning
confidence: 99%